Predictors of persistent high disease activity after methotrexate treatment in rheumatoid arthritis patients - Paramaiswari, Ayu; Kertia, Nyoman; Achadiono, Deddy; Sinarta, Armin; Nugroho, Dhite (Universa Medicina, 2025)
Background Methotrexate (MTX) is the firstline therapy for rheumatoid arthritis (RA). However, 30–40% of RA patients exhibit poor response. Identifying early factors associated with persistent disease activity is critical to guide treatment. This study aimed to identify predictors of persistent high disease activity (DAS28-ESR >3.2) after six months of MTX therapy in RA patients. Methods A retrospective cohort study was conducted involving 204 RA patients who had completed six months of MTX therapy. The primary outcome was DAS28-ESR score at six months. Independent variables included baseline erythrocyte sedimentation rate (ESR), cumulative doses of MTX and low-dose methylprednisolone (LDM), and rheumatoid factor (RF) status. Simple and multiple logistic regression was used to analyze the data.  Results Significant differences in ESR and cumulative MTX dose were observed between low and high disease activity groups. Multivariate analysis identified four independent predictors of persistent high disease activity (DAS28-ESR >3.2) after six months of MTX therapy: disease duration >11 months (AOR =0.45; 95% CI 0.23–0.89; p=0.025); age at onset >50 years (AOR 0.48; 95% CI 0.24–0.94; p=0.038); cumulative MTX dose >85 mg (AOR 4.75; 95% CI 1.55–14.64; p=0.006); ESR >66 mm/hr (AOR 2.32; 95% CI 1.11–4.89; p=0.026).  Conclusion Greater cumulative methotrexate dose (>85 mg) was the most influential predictor of persistent high disease activity (DAS28-ESR >3.2) after six months of MTX therapy in RA patients. These findings may assist clinicians in identifying patients at risk for poor MTX response and support timely therapeutic adjustments.